2018
DOI: 10.1007/s13311-018-0652-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms in Refractory Epilepsy During the First Year After Surgery

Abstract: Psychiatric morbidity in drug-resistant epilepsy is frequent. Surgery is the best therapeutic alternative for treating seizures, but the current evidence concerning the effects of surgery on psychiatric disorders (PDs) is inconclusive. We aim to clarify surgery's role in long-term PDs. Using a prospective controlled study, we analyzed the psychopathologic outcomes of patients with drug-resistant epilepsy, comparing those who underwent surgery to those who did not due to not being suitable. Surgical candidates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
(77 reference statements)
1
9
0
4
Order By: Relevance
“…Apesar dos casos de remissão, foi observado que em todos os estudos incluídos a porcentagem de casos de transtornos psiquiátricos no pós-operatórios continuou significante (Quadro 2). Inclusive, alguns estudos 11, [13][14][15] relataram um número maior de casos no pós-operatório quando comparado ao pré-operatório.…”
Section: Discussionunclassified
“…Apesar dos casos de remissão, foi observado que em todos os estudos incluídos a porcentagem de casos de transtornos psiquiátricos no pós-operatórios continuou significante (Quadro 2). Inclusive, alguns estudos 11, [13][14][15] relataram um número maior de casos no pós-operatório quando comparado ao pré-operatório.…”
Section: Discussionunclassified
“…69 Recently, a prospective study regarding cases with refractory epilepsy revealed that epilepsy surgery has beneficial outcomes on depression symptoms compared with control group after 12 months of postoperative followup. 70 Another confounding condition in diagnosis and treatment may be interictal symptoms. Preictal and postictal behavior changes may develop in some patients with epilepsy, temporal lobe, and other forms.…”
Section: Effect Of Antiepileptic Treatmentmentioning
confidence: 99%
“…On the other hand, epilepsy surgery is often the best therapeutic alternative for treating seizures, but the current evidence concerning its effects on mood is inconclusive: surgery could improve presurgical depressive symptoms or cause a relapse or de novo episodes of depression 42. A recent prospective controlled study on patients with refractory epilepsy showed that epilepsy surgery resulted in an improvement in depressive symptoms after 12 months follow-up compared to a control group 48Table 2Psychotropic Proprieties Of Antiepileptic DrugsAntiepileptic DrugMechanism Of ActionPsychotropic ActionMood EffectBarbituratesGABAergicNegative psychotropic actionBenzodiazepinesGABAergicNegative psychotropic actionVigabatrinGABAergicNegative psychotropic actionTiagabineGABAergicNegative psychotropic actionTopiramateVoltage-sensitive sodium channelGABAergic↓GlutammateNegative psychotropic actionLevetiracetamSynaptic vesicle SV2APresynaptic Calcium ChannelsNegative psychotropic actionZonisamideVoltage sensitive sodium channelsT-type Calcium channelsNegative psychotropic actionFelbamate+ GABAA receptors− NMDA receptorsNegative psychotropic actionPerampanelNon-competitive antagonist AMPA receptorisNegative psychotropic actionValproic acidVoltage dipendent sodium channelGABAergic effectMood-stabilizing+CarbamazepineVoltage sensitive sodium channels blockerSerotonin release/reuptake inhibitorMood-stabilizing+OxcarbazepineVoltage sensitive sodium channels blockerMood-stabilizing+LamotrigineVoltage sensitive sodium chann...…”
Section: Managementmentioning
confidence: 99%